THE SUBMODELING METHOD ANALYSIS ON POST-BUCKLING WEAR PREDICTION OF COMPRESSION COILED TUBING IN WELLBORE (MT) - LI Gang; SUN GuoHao; LIN Liang; YUE QianBei; ZHANG Qiang; WANG Gang (Jixie qiangdu)
Aiming at the problem of aggravated wear of coiled tubing caused by buckling in underground, a contact wear model between compression buckling coiled tubing and wellbore was established based on submodel method. Archard model was introduced to calculate the wear depth of coiled tubing. The removal process of material on the surface of coiled tubing was described by moving contact boundary node method to avoid mesh distortion.The wear of various compressive loads and annulus clearance are predicted.The results show that the coiled tubing is subjected to sinusoidal buckling and the wear parts are few, and the compression load and annular clearance have little influence on the wear of the coiled tubing.There are many and continuous wear parts in coiled tubing with spiral buckling, and the compression load and annulus clearance have great influence on the wear of coiled tubing This paper provides a calculation method for quantitative prediction of wear of buckling coiled tubing in wellbore.